COMMUNITY-BASED ECO-ENZYMES PRODUCTION: A STEP TOWARD A CLEAN AND SUSTAINABLE ENVIRONMENT: PEMBUATAN ECO-ENZIM BERBASIS KOMUNITAS: LANGKAH MENUJU LINGKUNGAN BERSIH DAN BERKELANJUTAN - Arshy Prodyanatasari; Krisnita Dwi Jayanti; Mely Purnadianti; Mardiana Prasetyani Putri; Jerhi Wahyu Fernanda (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: This community service activity focuses on the issue of processing household organic waste into valuable products, namely eco-enzyme. Waste can have an impact on human health, including a medium for transmission of diseases such as diarrhea and leptospirosis, decreased air quality. Objective: This activity aims to reduce the volume of household organic waste to reduce environmental pollution and improve the quality of life of the community and create valuable products. Method: The method used in this activity is Participatory Action Research (PAR) where the activity is divided into 2 sessions, namely counseling and demonstration activities. The activities were carried out on March 16 - July 20, 2024 and the targets of the activities were residents of Pojok Village, Kediri City as many as 45 people. Activities were carried out in partnership with Bank Sampah Sri Wilis. Results: In this activity, it was found that there was an increase in participant’s knowledge about household organic waste processing, especially in making eco-enzymes. This is known from the results of pretest and post-test scores which have increased significantly. Conclusion: Training activities on making eco-enzymes can be an alternative in processing organic waste into useful product innovations, reducing environmental pollution, and improving the quality of human life.